Kajian Penggunaan Maggot (Hermetiaillucens) Dalam Pakan Terhadap Kualitas Telur Ayam Ras: The Use of Black Soldier Flyer (Hermetia illucens) Larva in Feed of Eggs quality Laying Hens - Sumiati Sumiati; D. K. Purnamasari; Erwan Erwan; Syamsuhaidi Syamsuhaidi; K. G. Wiryawan; Dela Fatmala; Abu Thalib (LPPM Universitas Mataram, 2022)
This study aims to determine the effect of using Hermetia illucens maggot in feed on the internal and external quality of broiler eggs.The study used 80 laying hens aged 6 months which were divided into 4 treatments, 5 replications and each replication consisted of 4 tails. The variables observed were the external quality of eggs (egg weight, egg shape index, shell thickness, egg shell weight) and internal eggs (egg white index, yolk index, egg Haugh units, egg yolk color). The data obtained were analyzed with a completely randomized design. The average results of egg weight ranged from 56.18 g/egg - 56.98 g/egg, egg shape index between 73.91-80.54%, egg shell thickness between 0.35 mm – 0.38 mm, weight egg shells between 6.97 g/egg - 7.15 g/egg . While the egg white index ranged from 0.10 to 0.14, the yolk index ranged from 0.39 to 0.45, the Haugh unit ranged from 84.50 to 99.30, the yolk color ranged from 8.50 to 10.60. It was concluded that the use of Hermetia Illucens maggot 5%, 10%, 15% in feed resulted in external and internal quality of chicken eggs in the normal range.